The Effectiveness of Using Songs to Improve Vocabulary Acquisition in Primary School Students - Helmi (Sangkalemo : The Elementary School Teacher Education Journal, 2024)
This study investigates the effectiveness of using songs as a pedagogical tool to improve vocabulary acquisition among primary school students learning English as a foreign language. The research was conducted with a group of 40 students aged 8 to 10 at a public elementary school. The participants were divided into two groups: an experimental group, which was exposed to vocabulary learning through English songs, and a control group, which learned vocabulary through traditional methods such as rote memorization and textbook exercises. Data were collected over a period of six weeks using pre-tests and post-tests to measure vocabulary retention and acquisition. The findings revealed that students in the experimental group showed significantly higher improvement in vocabulary retention and usage compared to the control group. The results suggest that incorporating songs into language teaching not only makes learning more engaging and enjoyable but also enhances long-term vocabulary retention. Additionally, the study highlights the role of music in reducing anxiety and promoting a positive learning atmosphere in the classroom. In conclusion, the use of songs in teaching English vocabulary can be an effective strategy for primary school students, offering a fun and interactive way to reinforce language skills. Future research could explore the impact of different types of songs or expand the study to other language skills such as listening and speaking.